Asymmetric exchange rate pass-through in the Euro area: New evidence from smooth transition models - Nidhaleddine Ben Cheikh (Economics: The Open-Access, Open-Assessment E-Journal, 2012)
This paper examines the presence of asymmetric behavior in exchange rate pass-through (ERPT) to CPI inflation in 12 euro area (EA) countries. Using a class of nonlinear smooth transition models, the author tests for asymmetry with respect to the direction and the magnitude of exchange rate changes. On the one hand, the author finds only 5 out of 12 EA countries showing asymmetric pass-through related to exchange rate appreciations and depreciations. Results are somewhat mixed with no clear evidence about the direction of asymmetry. On the other hand, the author reports strong evidence that ERPT responds asymmetrically to the size of exchange rate changes as a result of presence of menu costs. The degree of ERPT is found to be higher for large exchange rate changes than for small ones in 9 out of 12 EA countries.
Keywords: C22; E31; F31; F41; 330; exchange rate pass-through; inflation; smooth transition regression models; euro area; Exchange Rate Pass-Through; Inflation; Lebenshaltungsindex; Eurozone